Pathological study of reproauctive system of cattle in Baghdad - Hatif, Saad Akram (The Iraqi Journal of Veterinary Medicine, 2000)
The genital organs of (89) Iraqi local cows. Collected from Al Tagi and Al- Mshahda areas of Baghdad region, were exmined for pathological pattern’s Gross abnormalities of genital tract were found to the uterine affection in the study had incidence (77) included other cases in other organs addition to inactive ovary 8 cases, follicular cyst (4) cases alone : 1-Inactive ovary 27 Cases 24% Luteal cyst 3 Cases 2.67% 2-Follicular cyst 14 Cases 12.46% Ovarian aplasia 3 Cases 2.67% 3-Ovario bursal adhesion 7 Cases 6.23% Para ovarian cys 1 Case 0.89% 4-Obstruction of the oviduct 3 Cases 2.67% Poysalpinx 1 Case 0.89% 5-Acute salpingitis 5 Cases 4.45% Chronic salpingitis 7 Cases 6.23% 6-Acute endometritis 5 Cases 4.45% Chronic endometritis 13 Cases 31.57% 7-Subacute endometritis 35 Cases 31.15% Pyometra 18 Cases 16% 8-Tuberculous metritis 2 Cases 1.78% Free martin 3 Cases 2.67% 9-Adenomyosis 1 Case 0.89% Uterus unicornus 1 Case 0.89% Cervesitis 17 Cases 15.43%